NAVIGATING IDENTITY POLITICS, DEMOCRACY, AND LEGAL CERTAINTY IN INDONESIA - Kartiko, Achmad; Simon Runturambi, Arthur Josias; Hanita, Margaretha; Syauqillah, Muhammad (Kanun Jurnal Ilmu Hukum, 2024)
Political identity has become a prominent phenomenon in Indonesia's democracy, especially since the Reformasi era, when political openness and freedom have been increasingly recognized. As a multicultural country, Indonesia faces the unique challenge of managing political identities that have the potential to foster solidarity but also risk triggering segregation and conflict. This study explores how political identity affects democracy in Indonesia and the enforcement of the rule of law, emphasizing legal certainty. In the legal context, certainty plays a critical role in maintaining social stability and ensuring equal rights for all citizens without discrimination, whether they are part of the majority or minority groups. Based on a normative approach and literature analysis, this research finds that identity politics in Indonesia often exploits religious and ethnic identities as political tools, sometimes disrupting the principles of equality, law enforcement, and democratic certainty. Legal reform is needed to strengthen human rights protections and create a fair, nondiscriminatory democratic space for all identity groups in Indonesia. It could create a void once the dominant political identity is weakened, allowing minority identities to rise, ultimately posing a new threat to democracy in Indonesia.